Padronização de um método imuno-histoquímico para confirmação da Leishmaniose tegumentar - Cibele Fontes Alves (2011)
Human Cutaneous Leishmaniasis, in America is known as American Tegumentar Leishmaniasis (LTA), is a cutaneous disease due an infectious agent, a protozoan of genus Leishmania where the amastigotes forms are able to multiply inside cells of mononuclear system of vertebrate host. The earlier and definitive diagnostic for LTA is fundamental to define the the patient treatment. At present, the diagnostic methods have shown low sensibility, laborious and time consuming. Thus, the aim of this study was to patronize an immunohistochemical parasitological method to LTA diagnostic. This study was based on another previously published immunohistochemistry method where it uses serum of a dog naturally infected with Leishmania infantum as primary antibody anti-Leishmania. 73 dermal biopsies samples of patients with LTA, from Caratinga/MG, were fixed in formol buffer solution (10%, pH=7,0) and included in paraffin. Previous parasitological exams were confirmed by positive dermal imprints stained by Giemsa and positive Montenegro Intradermal Reaction (IRM) test, All adult patients of both sex, living in rural zone nearest the forest, showed one to four classical cutaneous lesions of LTA, with 15 to 180 days ears old, mainly localized in external regions of the body as members and face. The immunohistochemistry method using serum hiperimune of dogs naturally infected with Leishmania infantum chagasi as a primary antibody anti-Leishmania was employed in all 73 skin samples. The immune reaction was revealed by the avindin-biotin peroxidase system. In parallel, histological and another immunohistochemistry method using monoclonal antibody anti-lipophosphoglican (LPG) of Leishmania, as a primary antibody, and the polymerase chain reaction (PCR) were carried out. The main histological epithelial alterations were acanthosis, papilomatois, hiperceratosis and parakeratosis. A mononuclear chronic and diffuse exudate composed by plasma cells, macrophages and lymphocytes were observed. In some cases giant cells (Langhans giant cells) could be found, but we did not find a classical granulomatous reaction in any case. The immunohistochemistry method proposal using was patronized because amastigotes forms of Leishmania where easily found in 91.78% of the skin biopsies samples wihout any kind of background. The parasitological diagnosis of LTA carried out the immunohistochemistry method patronized in this work showed higher sensibility than histology in comparison to Hematoxilin-Eosin analysis with 17.81% positive of cases and immunohistochemistry, using monoclonal anti-LPG with 71.23% positive of cases. PCR method revealed 100% of positive of cases, but these results were not statistical significant than the immunohistochemistry method patronized (p=0.7671) here. In addition, we use the polymer system free of biotin in the immunohistochemistry method patronized. It reduced the time consuming of the reaction in at least 06 hours in comparison to the classical protocol. We concluded the immunohistochemistry method patronized to define the parasitological diagnosis for LTA revealed high sensibility, lower time consuming and also less laborious than other diagnostic methods